2012
DOI: 10.1109/tse.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Essential Assumptions of Analogy-Based Effort Estimation

Abstract: Abstract-Background: There are too many design options for software effort estimators. How can we best explore them all? Aim: We seek aspects on general principles of effort estimation that can guide the design of effort estimators. Method: We identified the essential assumption of analogy-based effort estimation: i.e. the immediate neighbors of a project offer stable conclusions about that project. We test that assumption by generating a binary tree of clusters of effort data and comparing the variance of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 53 publications
1
163
0
Order By: Relevance
“…Therefore, the terms CC/WC should not be considered as synonyms of heterogeneous/homogeneous [30], and the possible heterogeneity of WC projects should be tackled. Menzies et al [21] and Minku and Yao [34] investigated the use of tree-based SEE models to tackle heterogeneity in general, i.e., not restricted to CC projects. Other local approaches such as k-nearest neighbours [2,40] could also be seen as tackling heterogeneity.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the terms CC/WC should not be considered as synonyms of heterogeneous/homogeneous [30], and the possible heterogeneity of WC projects should be tackled. Menzies et al [21] and Minku and Yao [34] investigated the use of tree-based SEE models to tackle heterogeneity in general, i.e., not restricted to CC projects. Other local approaches such as k-nearest neighbours [2,40] could also be seen as tackling heterogeneity.…”
Section: Related Workmentioning
confidence: 99%
“…Kocaguneli et al [22] investigated a tree-based filtering mechanism called TEAK [21] to tackle heterogeneity. This mechanism creates trees to represent training projects and provide effort estimations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Kocaguneli et al [43] concluded that an estimation that relies on a smaller number of more relevant analogues will result in better estimation performance than relying on a larger number of less relevant analogues. Our results are in agreement with Kocaguneli et al as LSA-X achieved significantly improved estimation performance.…”
Section: And Why Does It Work?mentioning
confidence: 99%
“…Data-intensive analogy based software effort prediction gained popularity in the late 1990's by Shepperd and Schofield. Recently, Kocaguneli et al (2011) proposed a method to improve Analogy based software estimation. Empirical experiments using the tools such as ESTOR and ANGEL (Keung, 2008) show that the estimation by analogy is a viable alternative to predict accuracy and flexibility.…”
Section: Introductionmentioning
confidence: 99%